Understanding the role of assembly factors in 30S subunit biogenesis - Thurlow, Brett Thomas (My University, 2016)
Our understanding regarding the function of YjeQ, RbfA, RimM and Era in ribosome biogenesis has been derived in part from the study of immature 30S particles that accumulate in bacteria strains lacking one of these factors. However, their mechanistic details are still unknown. Here, we demonstrate that the 30SΔyjeQ and 30SΔrimM immature particles are not dead-end products of assembly, but progress into mature 30S subunits. Mass spectrometry analysis revealed that in vivo the occupancy level of these factors in these immature 30S particles is below 10% and that the concentration of factors does not increase when immature particles accumulate in cells. Analysis of the binding interactions of these assembly factors with mature 30S subunits and the immature particles demonstrated that YjeQ and Era bind to the mature 30S subunit with high affinity, however binding of these factors to the immature particles and of RimM and RbfA to mature or immature particles is weak. This indicates that binding of the assembly factors to the immature particles is not occurring at physiological concentrations. These results suggest that in the absence of these factors, the immature particles evolve into a thermodynamically stable intermediate that exhibits low affinity for the assembly factors and that the true substrates of YjeQ, RbfA, RimM and Era are immature particles that precede the ribosomal particles accumulating in the knockouts strains. We also developed an Era-depletion and ΔrbfA strain, which exhibited slow-growth, cold-sensitivity and an aberrant ribosome profile, which are all characteristic of ribosome assembly defects. Cryo-EM structural analysis of the 30SEra-depleted particles revealed that multiple classes at various stages in the assembly process accumulate upon depletion of Era, suggesting that Era may have a global effect on biogenesis. Ultimately, this thesis provides new insights into the nature of 30S particles that accumulate during assembly factor perturbation and advances our understanding of ribosome biogenesis as a whole.
The role of assembly factors in 30S subunit biogenesis
Keywords: Ribosome Assembly